Hubungan Pengetahuan terhadap Kejadian Keputihan Pada Ibu Hamil di Poli Kia RSUD dr. Adjidarmo Kabupaten Lebak - Siti Aminah; Indah Yuliani (Malahayati Nursing Journal, 2024)
ABSTRACT One of the physiological changes that occur in pregnant women is vaginal discharge. Vaginal discharge in pregnant women often occurs due to adaptations and changes in the endocrine system in the body of pregnant women. Vaginal secretions are divided into 2 types: physiological and pathological. Physiological vaginal discharge is characterized by a small amount, clear, white (sometimes leaving yellow on the panties), odorless and not accompanied by itching, pain, swelling of the genitals, pain and swelling, pain when defecating. Based on a preliminary study of 17 respondents of 1st trimester and 2nd trimester pregnant women regarding the treatment of reproductive organs and vaginal discharge, 6 pregnant women experienced no vaginal discharge, 11 pregnant women experienced vaginal discharge. Knowing the relationship of knowledge to the incidence of vaginal discharge in pregnant women at the MCH poly of RSUD dr. Adjidarmo.  Data collection was carried out through questionnaires distributed to 30 respondents of pregnant women who experienced vaginal discharge. Cross sectional, non-experimental to see the correlation between the dependent variable and the independent variable. Data collection was carried out through questionnaires distributed to 30 respondents of pregnant women who experienced vaginal discharge. The population in this study was 30 pregnant women who experienced vaginal discharge within 2 months, with  a simple random sampling method. Statistical test obtained p-value 0.001 This proves that there is a relationship of Knowledge on the incidence of leucorrhoea in pregnant women at poly kia RSUD dr. Adjidarmo lebak district. The OR value obtained is  16,875  which means that  respondents who have poor knowledge of leucorrhoea have a 16.9 times greater risk for vaginal discharge, when compared to respondents who have good knowledge of leucorrhoea, with the results of Confidence Interval = 2,555 - 111,463. There is a relationship of knowledge on the incidence of leucorrhoea in pregnant women at the poly kia Regional General Hospital dr. Adjidarmo lebak district. It is hoped that the results of this study can increase knowledge for health workers that the importance of leucorrhoea knowledge for pregnant women who experience vaginal discharge. Keywords: Knowledge, Vaginal Discharge, Pregnant Women ABSTRAK Salah satu perubahan fisiologis yang terjadi pada ibu hamil adalah keputihan. Keputihan pada ibu hamil seringkali terjadi akibat adaptasi dan perubahan sistem endokrin pada tubuh ibu hamil. Sekresi vagina dibagi menjadi 2 jenis: fisiologis dan patologis. Keputihan fisiologis di tandai dengan jumlah yang sedikit, bening, berwarna putih (kadang meninggalkan warna kuning pada celana dalam), tidak berbau dan tidak disertai rasa gatal, nyeri, bengkak pada kemaluan, perih dan bengkak, rasa perih saat buang air. Berdasarkan studi pendahuluan terhadap 17 responden ibu hamil trimester 1 dan trimester 2 tentang perawatan organ reproduksi dan keputihan yaitu diperoleh 6 ibu hamil mengalami tidak mengalami keputihan, 11 ibu hamil mengalami keputihan. Mengetahui hubungan pengetahuan terhadap kejadian keputihan pada ibu hamil di poli KIA RSUD dr. Adjidarmo. Pengumpulan data dilakukan melalui kuesioner yang dibagikan kepada 30 responden ibu hamil yang mengalami keputihan.  Cross sectional, non-eksperimental untuk melihat korelasi antara variabel dependen dan variabel independent. Pengumpulan data dilakukan melalui kuesioner yang dibagikan kepada 30 responden ibu hamil yang mengalami keputihan. Populasi dalam penelitian ini adalah 30 ibu hamil yang mengalami keputihan dalam kurun waktu 2 Bulan, dengan metode simple random sampling. uji statistik diperoleh p-value 0,001 Hal ini membuktikan bahwa ada hubungan  Pengetahuan terhadap kejadian Keputihan pada ibu hamil di poli kia RSUD dr.Adjidarmo kabupaten lebak. Nilai OR yang diperoleh sebesar 16,875 yang berarti bahwa responden yang memiliki Pengetahuan Keputihan yang kurang baik tentang keputihan memiliki resiko 16,9 kali lebih besar untuk terjadinya keputihan, bila dibandingkan dengan responden yang memiliki pengetahuan yang baik tentang keputihan, dengan hasil Confidence Interval = 2.555 - 111.463. Adanya hubungan pengetahuan terhadap kejadian keputihan pada ibu hamil di poli kia Rumah Sakit Umum Daerah dr.Adjidarmo kabupaten lebak. Diharapkan hasil penelitian ini dapat menambah pengetahuan bagi tenaga kesehatan bahwa pentingnya pengetahuan keputihan terhadap ibu hamil yang mengalami keputihan. Kata Kunci: Pengetahuan, Keputihan, Ibu Hamil